Last Word: Ending the intergenerational transmission of body dissatisfaction and disordered eating: a call to investigate the mother-daughter relationship. Issue 6 (2nd November 2021) - Brun, Isabel; Russell-Mayhew, Shelly; Mudry, Tanya
ABSTRACT: The ubiquity and gravity of female body dissatisfaction and disordered eating has motivated countless academics and practitioners to better understand and treat these issues. Many researchers have found familial, and more specifically maternal influence, to impact daughters' development of body dissatisfaction and disordered eating. Researchers have demonstrated that mothers who struggle with body dissatisfaction and disordered eating tend to transmit and reinforce harmful weight-related attitudes and behaviours to their daughters, which has been found to result in the development of daughters' own body dissatisfaction and disordered eating. Regardless of these findings, little research has been conducted to explore the ways in which mothers can attempt to end the intergenerational transmission of body dissatisfaction and disordered eating to daughters. As such, in this article, we call researchers and practitioners to fill this gap in knowledge.